Analysis of CBR design value selection methods on flexible pavement design: Colombia case study - Mora L., Otto; Murillo A., Michel; Rosania A., Tiana; CastaÃ±eda A., Abraham; Pinto C., Rosa; Padilla M., Andrea (International Journal of Engineering and Technology, 2020)
A comparative analysis was carried out to observe the variation of a flexible pavement structural thickness, due to the use of different meth-ods to calculate the CBR design value, as an essential variable to estimate the Subgrade Resilient Modulus (Mr) through an empirical corre-lation. The Asphalt Institute Method and the Mean Criterion Method were applied to calculate de Design CBR value of a homogeneous roadway division from a representative track section located in the Bolivar Department, Colombia. As a result, the Design Percentiles of the CBR design unit were expanded for the Asphalt Institute method, thus, allowing the approach of more reliable and safe designs, considering that this method limits the selection percentiles to three traffic levels.Â Â